The Impact of Psychological Wellbeing and Organisational Climate on Employee Performance through Job Satisfaction - Wandra, Adi; Heliyani (Al-Qalam Institue, 2025)
This study aims to analyse the influence of psychological well-being and organisational climate on employee performance through job satisfaction, with a specific focus on the context of educational management. Using a quantitative approach with a survey method, the research involved 58 executive staff members—comprising general administrative officers, assistant treasurers, and data processors—selected through total sampling. Data were gathered via a structured questionnaire assessing psychological well-being, organisational climate, job satisfaction, and performance. The analysis employed descriptive statistics and Structural Equation Modelling (SEM) with Partial Least Squares (PLS). Results revealed that psychological well-being (β = 0.365, p = 0.056) and organisational climate (β = 0.168, p = 0.316) both have a positive but statistically insignificant impact on performance. However, these factors significantly influence job satisfaction (p = 0.000), which in turn significantly affects performance (β = 0.368, p = 0.012). The findings underscore the pivotal mediating role of job satisfaction in enhancing employee performance within educational institutions, highlighting the importance of fostering a supportive work environment and psychological well-being to improve outcomes in the education sector.